2020
DOI: 10.1111/liv.14670
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐complication diagnosis of hepatitis C infection: Risk factors and trends over time

Abstract: Background & Aims: Hepatitis C virus (HCV) is a common and treatable cause of cirrhosis and its complications, yet many chronically infected individuals remain undiagnosed until a late stage. We sought to identify the frequency of and risk factors for HCV diagnosis peri-complication, that is within six months of an advanced liver disease complication. Methods: This was a retrospective cohort study of Ontario residents diagnosed with chronic HCV infection between 2003 and 2014. HCV diagnosis peri-complication w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…We find this particular result surprising and different from our observation from the US In one study using data from the National Health and Nutrition Examination Survey (NHANES) (1999-2016), we found that HCV prevalence has decreased over time in whites and blacks but not in other race/ethnicities, foreign-born or those born after 1985. 2 In another study of 798 HCV-related HCC patients among whom 28% were Asian and among these, 99% foreign-born, we found that However, like Lapointe-Shaw et al, 1 we also found that many of the HCV diagnoses were determined when patients presented with later stages of liver disease, which in many cases did not allow for an option of a curative treatment. 2,3 Thus, we agree that universal screening as already recommended in the US (all adults aged ≥ 18 years) should be considered, especially since it has been cost-effective, especially since there is now an excellent curative treatment available.…”
Section: Delayed Diagnosis and Disparity In Hepatitis C Virus-infectesupporting
confidence: 44%
See 1 more Smart Citation
“…We find this particular result surprising and different from our observation from the US In one study using data from the National Health and Nutrition Examination Survey (NHANES) (1999-2016), we found that HCV prevalence has decreased over time in whites and blacks but not in other race/ethnicities, foreign-born or those born after 1985. 2 In another study of 798 HCV-related HCC patients among whom 28% were Asian and among these, 99% foreign-born, we found that However, like Lapointe-Shaw et al, 1 we also found that many of the HCV diagnoses were determined when patients presented with later stages of liver disease, which in many cases did not allow for an option of a curative treatment. 2,3 Thus, we agree that universal screening as already recommended in the US (all adults aged ≥ 18 years) should be considered, especially since it has been cost-effective, especially since there is now an excellent curative treatment available.…”
Section: Delayed Diagnosis and Disparity In Hepatitis C Virus-infectesupporting
confidence: 44%
“…We read with interest the recent paper by Lapointe-Shaw et al, 1 which reported that peri-complication HCV diagnosis which occurred within ±6 months of developing decompensated cirrhosis, hepatocellular carcinoma (HCC) or undergoing a liver transplant occurred in 4.2% of those with HCV diagnosis (1,645/39,515), which was 31.6% of the total cases with end-stage complications (1,645/5,202). In addition, they found only 2.9% (n = 133) of those with peri-complication diagnoses were immigrants and that immigrants were less likely to have been diagnosed with HCV as a result of presenting with end-stage liver complications.…”
Section: Delayed Diagnosis and Disparity In Hepatitis C Virus-infectementioning
confidence: 99%
“…Moving forward, it will be important to ensure that the lack of in‐person visits and ongoing restrictions and barriers to seeking care do not lead to reduced testing for viral hepatitis, as high screening rates lead to earlier diagnosis and reduced preventable complications. Ongoing tracking of testing trends will be critical to guide strategies to improve testing rates, and ensure elimination efforts do not stagnate further 9,10 …”
Section: Discussionmentioning
confidence: 99%
“…Ongoing tracking of testing trends will be critical to guide strategies to improve testing rates, and ensure elimination efforts do not stagnate further. 9,10 There are limitations to the study. PHO does not conduct all HBV and HCV serological testing.…”
Section: Significance Statementmentioning
confidence: 99%
“…The fact that over 50% of the patients in our study had decompensated cirrhosis lends further evidence that HCV‐related HCC was found late in the course of disease, similar to a prior study that found a high peri‐complication diagnosis rate of 32% among HCV patients. Additionally, only 58.5% of patients with positive HCV RNA at HCC diagnosis received DAA treatment in this study, further highlighting the severely suboptimal treatment rate even among patients with confirmed viraemic HCV‐related HCC 18,19 . As such, the low treatment rate demonstrates the need for continual education among practitioners and the public about the need to screen for HCV as well as the availability of potentially curative treatment with relatively mild side effects 20–26 .…”
Section: Discussionmentioning
confidence: 85%